The Embodying Deep Learning in Pancasila Student Profile - Jamaludin, Jaja (Journal of Education and Learning Mathematics Research (JELMaR), 2025)
Education in Indonesia faces challenges in shaping students' characters according to the values ​​of the Pancasila Student Profile. The lack of learning approaches that support deep understanding and critical thinking skills is one of the main obstacles in the implementation of character education. This article examines the application of Deep Learning in learning as an innovative strategy to strengthen the internalization of Pancasila values. Using the literature study method, this study analyzes the concept of Deep Learning, the challenges of its implementation, and the opportunities for its application in the Indonesian education system. The results of the study indicate that Deep Learning can improve conceptual understanding, high-level thinking skills, and active student involvement in the learning process. Therefore, the integration of Deep Learning in Pancasila-based character education has the potential to be an effective solution in facing the challenges of 21st-century learning. This article provides recommendations for educators and policy makers in designing learning strategies that are more contextual, reflective, and oriented towards problem-solving.